Osteotendinous repair of bilateral spontaneous quadriceps tendon ruptures with the Krackow technique in two patients with chronic renal failure - Kara, Adnan; Sarı, Seçkin; Şeker, Ali; Öztürk, İrfan (Turkish Society of Orthopaedics and Traumatology, 2013)
Although unilateral traumatic quadriceps tendon rupture is a relatively frequent pathology, bilateral non-traumatic spontaneous ruptures are uncommon and are usually associated with chronic renal failure, hyperparathyroidism, gout, and systemic lupus erythematosus. This paper aimed to discuss two patients with chronic renal failure treated with the Krackow suture technique for spontaneous bilateral quadriceps tendon rupture.

Tek taraflı travmatik kuadriseps tendon rüptürü göreceli olarak sık rastlanılan ortopedik bir patoloji olmasına rağmen iki taraflı, travma olmaksızın spontan gelişen rüptürler oldukça nadirdir ve sıklıkla altında kronik renal yetmezlik, hiperparatiroidizm, gut ve sistemik lupus eritematozus gibi sistemik hastalıklar yatmaktadır. Bu olgu sunumunda spontan iki taraflı kuadriseps tendon rüptürü gelişen ve Krackow yöntemiyle osteotendinöz onarım uygulanan, kronik böbrek yetmezlikli iki hasta değerlendirilmiştir.
Kronik böbrek yetmezlikli iki hastada spontan çift taraflı kuadriseps tendon rüptürünün Krackow yöntemiyle osteotendinöz onarımı
Keywords: Bilateral Tendon Rupture; Krackow Technique; Quadriceps; İki Taraflı Tendon Rüptürü; Krackow Tekniği; Kuadriseps